Evaluation of Students’ Needs in the Teaching Methodology English Language TeacherTraining Curriculum in Algeria - DJOUIMA, Leila (Journal of Human Sciences, 2016)
This paper seeks to contribute to discussions on the development of teacher training curricula by evaluating the trainees’ needs within the English language teacher training teaching methodology curriculum in Algeria. The purpose is to evaluate the teaching methodology curriculum in terms of its response to the students’ needs and expectations, hypothesizing that needs assessment in this context is a matter of developers’ perceptions where the other stakeholders’ views including students’ felt needs and educational experts attitudes are neglected. The curriculum is evaluated through the analysis of three questionnaires addressed to teachers, English supervisors in Eastern and Southern Algeria, and final year trainees at the Ecole Normale Superieure (ENS) of Constantine. The analysis of the questionnaires has confirmed the hypothesis stated above